Occupational exposure to formaldehyde and alterations in lymphocyte subsets12. Issue 2 (5th July 2012) - Hosgood, H. Dean; Zhang, Luoping; Tang, Xiaojiang; Vermeulen, Roel; Hao, Zhenyue; Shen, Min; Qiu, Chuangyi; Ge, Yichen; Hua, Ming; Ji, Zhiying; Li, Senhua; Xiong, Jun; et al.
Abstract Background Formaldehyde is used in many occupational settings, most notably in manufacturing, health care, and embalming. Formaldehyde has been classified as a human carcinogen, but its mechanism of action remains uncertain. Methods We carried out a cross‐sectional study of 43 formaldehyde‐exposed workers and 51 unexposed age and sex‐matched controls in Guangdong, China to study formaldehyde's early biologic effects. To follow up our previous report that the total lymphocyte count was decreased in formaldehyde‐exposed workers compared with controls, we evaluated each major lymphocyte subset (i.e., CD4+ T cells, CD8+ T cells, natural killer [NK] cells, and B cells) and T cell lymphocyte subset (CD4+ naïve and memory T cells, CD8+ naïve and memory T cells, and regulatory T cells). Linear regression of each subset was used to test for differences between exposed workers and controls, adjusting for potential confounders. Results Total NK cell and T cell counts were about 24% (P = 0.037) and 16% (P = 0.0042) lower, respectively, among exposed workers. Among certain T cell subsets, decreased counts among exposed workers were observed for CD8+ T cells (P = 0.026), CD8+ effector memory T cells (P = 0.018), and regulatory T cells (CD4+FoxP3+: P = 0.04; CD25+FoxP3+: P = 0.008). Conclusions Formaldehyde‐exposed workers experienced decreased counts of NK cells, regulatory T cells, and CD8+ effector memory T cells; however, due to the small sample size; these findings need to be confirmed in larger studies. Am. J. Ind. Med. 56:252–257, 2013. © 2011 Wiley Periodicals, Inc.